Efforts to Improve Students’ Understanding of Algebraic Operations through the Jigsaw Cooperative Learning Model - Azizah, Riska Binti Fatatin; Yusniati, Devi; Syadidul Itqan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This classroom action research aimed to improve students’ understanding of algebraic operations through the implementation of the Jigsaw cooperative learning model. The study was conducted in two cycles involving 12 students of class XII at MA Islamiyah Syafi’iyah during the 2025/2026 academic year. Each cycle consisted of four stages: planning, action, observation, and reflection. Data were collected through observation, tests, interviews, and documentation, and analyzed using qualitative and quantitative approaches. The findings show significant improvement in students’ conceptual understanding and learning participation. Students became more active in discussions, questioning, and peer teaching activities. The average score increased from 64 in the initial condition to 72 in Cycle I, and further improved to 82 in Cycle II. The percentage of students achieving mastery learning rose from 33.3% to 86.7% after the implementation of the Jigsaw model. These results indicate that the Jigsaw cooperative learning model is effective in enhancing students’ understanding of algebraic operations. The model also fosters collaboration, communication skills, and student responsibility in the learning process.